PUBLIC POLICY BY WILLIAM DUNN: ANALYSIS AND IMPLEMENTATION - Yanti Fatmariyanti; Anis Fauzi (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Analysis of Policy is the activity of creating knowledge about and in the policy-making process, which examines the causes, effects, and performance of public policies and programs. In its application, public policy often encounters obstacles both internal and external to those implementing the policy, so it is necessary to study how the implementation of public policy is related to the factors and dimensions that influence it. this article aims to find out what is public policy analysis according to William Dunn and its implementation. The writing method in this study uses qualitative research methods, by conducting literature searches, searching relevant sources and searching data via the internet, electronic media, and some relevant literature. The results of the study illustrate that policy analysis needs to be carried out before public policies are issued and it is necessary to disseminate the substance or socialization of these policies, as a basis for knowledge and understanding before the policy implementation process is carried out.